Characteristics and outcomes of older patients with coronavirus disease 2019 in Japan. Issue 8 (9th June 2021) - Tanaka, Kenta; Zha, Ling; Kitamura, Tetsuhisa; Katayama, Yusuke; Takeuchi, Taro; Komukai, Sho; Hirayama, Atsushi; Shimazu, Takeshi; Sobue, Tomotaka; ,
Abstract : Aim: The epidemiological characteristics, in‐hospital treatments and outcomes of coronavirus disease 2019 among older patients have not been fully evaluated in Japan. Methods: In this retrospective observational study carried out in Osaka Prefecture, Japan, we enrolled patients aged ≥60 years with laboratory‐confirmed coronavirus disease 2019 from January to November 2020. The main outcome was mortality during the observation period, based on the Infectious Diseases Control Law. Cox regression analysis was used to evaluate the association between epidemiological factors and mortality among older patients with coronavirus disease 2019. Results: Older patients accounted for 21.5% (3192/14 846) of the registered patients with coronavirus disease 2019. The number of patients according to age was as follows: 60–69 years, 1140 (35.7%); 70–79 years, 1058 (33.1%); 80–89 years, 749 (23.5%); and ≥90 years, 245 (7.7%). The proportion of deaths during the observation period was 8.5% (271/3192). The proportion of deaths increased with increasing age category (from 1.9% to 20.4%, P for trend <0.001). In multivariable Cox regression analysis, patients aged 70–79, 80–89 and ≥90 years had higher hazard ratios and 95% confidence intervals of death (2.62 [1.63–4.23], 5.99 [3.77–9.50] and 10.24 [6.03–17.40], respectively) than those aged 60–69 years. Factors such as male sex, presence of comorbidities, cluster cases in medical institutions and moderate/severe symptoms at diagnosis were also associated with mortality. Conclusions: This study shows the epidemiological characteristics of older patients with coronavirus disease 2019 in Osaka Prefecture, Japan. The proportion of deaths was 8.5% in total and increased with increasing age. Geriatr Gerontol Int 2021; 21: 629–635 .